The impact of wrist joint movement on stroke effect during topspin forehand in table tennis - Zheng, C.; Lu, M.; Zeng, Y.; Hu, M.; Geng, X.; Xiao, Y. (International Journal of Performance Analysis in Sport, 2021)
The main purpose of this study was to explore the impact of the wrist joint movement on the stroke effect, especially that of the angular velocity and linear velocity on the ball speed and spin speed. Thirty-two young table tennis players were randomly selected from China Table Tennis College. The high-speed infrared motion capture system was used to collect the real-time data of the wrist joint movement during the stroke, and the high-speed camera was used to measure the spin speed. The influence of the wrist joint movement on the stroke effect was analysed. The results of this study showed that the linear velocity of the right wrist joint was positively correlated with ball speed (r = 0.283, p < 0.01) and spin speed (r = 0.162, p = 0.032). The angular velocity of the right wrist joint had a significant positive correlation with the ball speed (r = 0.251, p = 0.015) and spin speed (r = 0.391, p < 0.01). The results of this study further explained the mechanism of power transfer by the kinetic segment-chain, which provided a valuable reference for formulating targeted training plans for young table tennis players.